Design of a Dual Band Miniature Microstrip Patch Antenna. Issue 1 (February 2021) - Akhil, Kataru; Sudeer, Adabala; Nagendram, S; Kalyan, SSS
Abstract: Microstrip patch antennas perform a major task in current communication techniques. In this paper we mainly specify the model of a dual-band miniature MPA for IoT application. The specific antenna is fed through a 50Ω microstrip line feed. And the architectural layout, and simulation of the expected antenna are done using HFSS software. The ground volume of the planned antenna is 10×6.5mm2. The projected antenna having a relative permittivity of 4.4 on the FR4 epoxy surface, 0.02 loss tangent, and 1.6 mm height. The antenna has a managing frequency ranging from 5.8GHz to 14GHz with -35.84dB return loss and -17.17dB respectively. And studied in terms of gain and VSWR. The general configuration of the suggested antenna is applicable for easy designing and it can be utilized for Ku-band satellite applications, weather monitoring systems, etc.